Terrestrial Rabies and Human Postexposure Prophylaxis, New York, USA - Eidson, Millicent (Centers for Disease Control and Prevention, 2010)
During 1993–2002, cats accounted for 2.7% of rabid terrestrial animals in New York but for one third of human exposure incidents and treatments. Nonbite exposures and animals of undetermined rabies status accounted for 54% and 56%, respectively, of persons receiving rabies treatments.